A polyacetylene from Gymnaster koraiensis exerts hepatoprotective effects in vivo and in vitro - Lee, Saet Byoul; Kang, Kyungsu; Oidovsambuu, Sarangerel; Jho, Eun Hye; Yun, Ji Ho; Yoo, Ji-Hye; Lee, En-Ha; Pan, Cheol-Ho; Lee, Jae Kwon; Jung, Sang Noon; Nho, Chu Won (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
In the present study, we isolated a polyacetylene, gymnasterkoreayne B (GKB), from Gymnaster koraiensis and investigated the effect of GKB on the protection from oxidative stress-induced cytotoxicity through induction of the expression of cellular defense enzymes. GKB induced mRNA expression and enzyme activity of NAD(P)H:quinone oxidoreductase (NQO1) in vitro and in vivo, and potently increased expression of many cellular defense genes including glutathione-S-transferases, UDP-glucuronosyltransferase, and glutathione reductase (GSR) in normal rat liver. The nuclear factor erythroid 2-related factor 2 (Nrf2) which is known to induce various antioxidant and cytoprotective genes, and the genes containing the antioxidant response element (ARE), including NQO1, hemeoxygenease-1, GSR were induced by GKB in HepG2 human hepatocarcinoma cells. Pre-treatment of the cells with GKB accelerated the production of glutathione and mitigated menadione-induced cytotoxicity in HepG2 cells. Taken together, we found that GKB was a novel inducer of phase II detoxification enzymes and cellular defense enzymes, resulting in protection of the cells from oxidative stress and hepatotoxicity through regulation of detoxifying and antioxidant systems. (C) 2010 Published by Elsevier Ltd.
Keywords: DRUG-METABOLIZING-ENZYMES; OXIDATIVE STRESS; TRANSCRIPTIONAL REGULATION; NAD(P)H-QUINONE REDUCTASE; INDUCIBLE EXPRESSION; RESPONSIVE ELEMENT; CANCER CELLS; BASAL LEVEL; PHASE-I; GENE